Emotion Regulation and Impulse Control of Child Victims of Sexual Harassment in Makassar City - Suhayni Syahran Muhamad (Journal of Public Health and Pharmacy)
This study aims to describe the regulation of emotions and impulse control in child victims of sexual abuse. This research is a qualitative research with a case study approach. Data were obtained through in-depth interviews, unstructured observation and documentation to 10 informants consisting of child victims of sexual abuse, families of child victims of sexual abuse, P2TP2A officers, and health workers in Makassar City. Content analysis is used to identify topics or categories in data. The results showed that child victims of sexual abuse can regulate their emotions and control impulses well if they get help from their surroundings, especially their families. Child victims of sexual abuse are able to be optimistic and never give up because they have a desire to make their parents happy and reach their dreams in the future. It was concluded that emotional support and social support for child victims of sexual abuse play an important role in the formation and improvement of emotional regulation and impulse control in children victims of sexual abuse in the future.